Double-cycle nano-structure coating as well as preparation method and application thereof
By using a bicyclic nanostructured coating on the cutting tool, the problem of choice between hardness and binding force of nano-multilayer coating is solved, and the effects of high hardness, high wear resistance and high binding force are achieved, which significantly improves the service life of the tool.
Patent Information
- Application Number
- CN202411888529.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
The existing nano multilayer coatings face the problem of choice between the thickness of the nanolayer, the performance of hardness and binding force on the structure, and it is difficult to have high hardness, high wear resistance and high binding force at the same time.
The bicyclic nanostructure coating is adopted, and the thickness relationship between the first component thick layer, the second component thin layer, the first component thin layer and the second component thick layer is specially arranged, and combined with the physical vapor deposition technology, the structure is formed on the cutting tool.
The bicyclic nanostructured coating has both the superhard effect of thin periodic coating and the high toughness and high binding force of thick periodic coating, which significantly improves the service life of cutting tools.
Smart Images

Figure CN119663181A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of coatings and relates to a nanostructured coating, in particular to a double-period nanostructured coating and a preparation method and application thereof. Background Art
[0002] With the development of cutting tool technology, people have put forward higher and higher requirements on the materials and performance of cutting tools, and need to obtain cutting tools with high hardness, high wear resistance, high toughness and high precision. Depositing coatings on the surface of cutting tools through physical vapor deposition (PVD), chemical vapor deposition (CVD) and other technologies has become an important direction for the development of modern cutting tools. As an important component of cemented carbide cutting tools, coatings are closely related to the performance of cutting tools together with substrates and grooves. Stable coatings can significantly improve the service life and processing efficiency of cutting tools.
[0003] TiAlN coating can improve the cutting performance and service life of the tool. With the development of PVD technology, the coating continues to go deeper from a single layer to a multilayer, nanostructure, etc., and nanocomposite coatings with higher hardness, stronger wear resistance, and special nanostructures are invented and paid attention to. For example, the existing more commonly used TiAlMeN-TiAlN nano multilayer coating is a coating system composed of nanolayers of two different materials and structures such as TiAlMeN and TiAlN with nanoscale. The coating has a periodicity of nanometer scale in the thickness direction and has a basically fixed superlattice period of a double-layer thickness. Compared with single-layer and multilayer structure coatings, due to the Hall-Petch relationship caused by the nanoscale in the structure, it shows superhardness and supermodulus effect in mechanical properties, has superhardness that other coatings do not have, and can improve wear resistance.
[0004] Most existing nano-multilayer coatings are single-period, which means that the thickness and thickness relationship between the two nano-layers of different materials and / or structures are usually constant in the same coating. Under the same composition process, when the thickness of the nano-layer is thinner, it will bring smaller nano-scale grains to the coating, and according to the Hall-Page relationship, it will show stronger superhard effect and wear resistance; but thinner nano-thickness also means that in the coating structure of the same thickness, the number and density of interfaces between the nano-layers are also higher. Due to the interfaces between different nano-layers, the lattice structure, lattice constant, etc. usually change too quickly and frequently, which significantly increases the internal stress between the coatings, making the coatings on the interface insufficient in bonding strength and poor in toughness. In actual applications, they are easy to fall off under high temperature and high impact.
[0005] Therefore, under the same other conditions, when the nano-thickness of a single-period nano-multilayer coating is thin and the period is short, the coating exhibits high hardness and high wear resistance in application, but the bonding force is insufficient and easy to peel off. When the nano-thickness is thick and the period is long, the coating exhibits good bonding force and is not easy to peel off in application, but the hardness and wear resistance are reduced. In coating design and application, it faces the trade-off problem between the thickness of the nano-layer in structure and the hardness and bonding force of the coating in performance.
[0006] Therefore, how to design a nanostructured coating so that it has a sufficiently thin nano-thickness layer to provide high hardness and high wear resistance, and has a sufficiently small interface between coatings to provide bonding strength is a technical problem that urgently needs to be solved in this field. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a dual-period nanostructured coating and a preparation method and application thereof. The dual-period nanostructured coating has both the superhard effect of a thin periodic coating and the high toughness and high bonding strength of a thick periodic coating by specifically setting the first component thick layer, the second component thin layer, and the thickness relationship between the first component thin layer and the second component thick layer. When the dual-period nanostructured coating is applied to cutting tools, the service life of the cutting tools can be significantly improved.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a dual-periodic nanostructure coating, which includes periodic coating units stacked in sequence; the periodic coating units include a first component thick layer, a second component thin layer, a first component thin layer and a second component thick layer stacked in sequence.
[0010] The thickness of the first component thick layer is greater than the thickness of the first component thin layer, and the thickness of the first component thick layer is greater than the thickness of the second component thin layer; the thickness of the second component thick layer is greater than the thickness of the second component thin layer, and the thickness of the second component thick layer is greater than the thickness of the first component thin layer.
[0011] The dual-period nanostructured coating provided by the present invention has both the superhard effect of the thin periodic coating and the high toughness and high bonding strength of the thick periodic coating by specifically setting the first component thick layer, the second component thin layer, and the thickness relationship between the first component thin layer and the second component thick layer. When the dual-period nanostructured coating is applied to cutting tools, the service life of the cutting tools can be significantly improved.
[0012] Specifically, the thickness of the first component layer a nm, the thickness of the second component layer b nm, and the thickness of the single-period layer c = (a + b) nm of the existing single-period nanostructured coating are constant values, and the number of nanolayer interfaces per unit thickness (taking 1 μm = 1000 nm as an example) 1000 / c is also a constant value. Among them, the size of a and b affects the hardness and wear resistance of the coating, and the size of the number of nanolayer interfaces per unit thickness 1000 / c affects the toughness and bonding force of the coating. The technical solution of the present invention subdivides the periodic structure, with the first component thick layer and the second component thin layer as the first small period, and the first component thin layer and the second component thick layer as the second small period. Through the specific thickness settings of the first component thick layer, the second component thin layer, and the first component thin layer and the second component thick layer, it is possible to obtain a first component thin layer and a second component thin layer that are thinner than the single-period nanostructured coating when the number of nanolayer interfaces per unit thickness is not much different; based on the Hall-Petch relationship, the hardness of the first component thin layer and the second component thin layer is improved to improve the average hardness of the double-period nanostructured coating. Therefore, compared with the single-period nanostructured coating, the double-period nanostructured coating provided by the present invention can significantly improve the hardness while maintaining little difference in toughness and bonding strength.
[0013] In order to ensure that the double-periodic nanostructured coating significantly improves hardness while maintaining little difference in toughness and bonding strength, relatively thin first component thin layers and second component thin layers, as well as relatively thick first component thick layers and second component thick layers are required.
[0014] Preferably, the thickness of the first component thick layer is a1 nm, the thickness of the second component thin layer is b1 nm, the thickness of the first component thin layer is a2 nm, and the thickness of the second component thick layer is b2 nm.
[0015] When the thickness of the first component thick layer, the thickness of the second component thin layer, the thickness of the first component thin layer and the thickness of the second component thick layer satisfy a1 / a2≥1.5, b2 / b1≥1.5, a1 / b1≥1.5 and b2 / a2≥1.5, the hardness improvement provided by the thinner first component thin layer and the second component thin layer can obviously cover the hardness attenuation of the first component thick layer and the second component thick layer, so that the overall hardness of the coating is significantly improved; however, when the thickness difference between the first component thick layer, the second component thin layer, and the first component thin layer and the second component thick layer is too large, it will lead to the microstructural tendency of the phase composition and lattice constant of the second component thin layer Epitaxial growth on the basis of the first component thick layer causes lattice distortion of the second component thin layer, which will increase the hardness of the dual-periodic nanostructured coating, but will also cause the resistance of the dual-periodic nanostructured coating to decline, thereby causing the bonding force of the dual-periodic nanostructured coating to be greatly reduced. Therefore, as a further preferred technical solution of the present invention, the thickness of the first component thick layer, the thickness of the second component thin layer, the thickness of the first component thin layer and the thickness of the second component thick layer satisfy: 1.5≤a1 / a2≤3, 1.5≤b2 / b1≤3, 1.5≤a1 / b1≤3, 1.5≤b2 / a2≤3.
[0016] Among them, 1.5≤a1 / a2≤3, for example, it can be 1.5, 1.8, 2, 2.4, 2.5, 2.8 or 3, but is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0017] 1.5≤b2 / b1≤3, for example, it can be 1.5, 1.8, 2, 2.4, 2.5, 2.8 or 3, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] 1.5≤a1 / b1≤3, for example, it can be 1.5, 1.8, 2, 2.4, 2.5, 2.8 or 3, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] 1.5≤b2 / a2≤3, for example, it can be 1.5, 1.8, 2, 2.4, 2.5, 2.8 or 3, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] On the premise that the first component thick layer, the second component thin layer, and the first component thin layer and the second component thick layer satisfy the above relationship, as a further preferred technical solution, the thickness of the first component thick layer is 4nm-70nm, the thickness of the second component thin layer is 4nm-70nm, the thickness of the first component thin layer is 4nm-70nm, and the thickness of the second component thick layer is 4nm-70nm.
[0021] The thickness of the first component thick layer is 4nm-70nm, for example, 4nm, 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm or 70nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] The thickness of the second component thin layer is 4nm-70nm, for example, 4nm, 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm or 70nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] The thickness of the first component thin layer is 4nm-70nm, for example, 4nm, 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm or 70nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] The thickness of the second component is 4nm-70nm, for example, it can be 4nm, 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm or 70nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] Preferably, the first component thick layer and the second component thin layer form a first small period, and the first component thin layer and the second component thick layer form a second small period, and the thickness of the first small period is equal to or similar to the thickness of the second small period.
[0026] When the thickness of the first small period, the second small period or the single-layer periodic structure is too thin, the number of nanolayer interfaces per unit thickness is too large, and the toughness and bonding strength of the coating are poor; and when the thickness of the first small period, the second small period or the single-layer periodic structure is too thick, the hardness of the coating decreases. Therefore, it is necessary to optimize the thickness of the first small period, the second small period and the single-layer periodic structure.
[0027] Preferably, the total thickness of the first component thick layer and the second component thin layer is 12nm-100nm, for example, it can be 12nm, 15nm, 20nm, 30nm, 40nm, 50nm, 60nm, 80nm or 100nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] Preferably, the total thickness of the first component thin layer and the second component thick layer is 12nm-100nm, for example, it can be 12nm, 15nm, 20nm, 30nm, 40nm, 50nm, 60nm, 80nm or 100nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the total thickness of the first component thick layer, the second component thin layer, and the first component thin layer and the second component thick layer is 24nm-200nm, for example, it can be 24nm, 30nm, 40nm, 60nm, 80nm, 100nm, 120nm, 160nm or 200nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] In the present invention, the first component of the first component thick layer, the second component thin layer, the first component thin layer and the second component thick layer is different from the second component.
[0031] Preferably, the first component in the first component thin layer and the first component thick layer is independently M1 a M2 b M3 c M m .
[0032] M1 includes any one of Ti, Cr, Zr, Hf, W or Mo.
[0033] M2 includes Al.
[0034] M3 includes any one of Ti, Cr, Zr, Hf, V, Ta, Nb, W, Mn, Mo or Si, or a combination of at least two of them. Typical but non-limiting combinations include a combination of Ti and Cr, a combination of Zr and Hf, a combination of V and Ta, a combination of Nb and W, a combination of Ti, Cr, Zr and Hf, a combination of Ta, Nb, W, Mn, Mo and Si, or a combination of Ti, Cr, Zr, Hf, V, Ta, Nb, W, Mn, Mo and Si.
[0035] M is any one of N, O, C or B or a combination of at least two thereof. Typical but non-limiting combinations include a combination of N and C, a combination of N and B, a combination of C and B, or a combination of N, C and B.
[0036] a>0.3, b>0.3 or b=0, c≤0.2, and a+b+c=1.
[0037] When M is N and / or C, 0.95≤m≤1.05.
[0038] When M is O, 1.45≤m≤1.55.
[0039] When M is B, 1.95≤m≤2.05.
[0040] Preferably, the second components in the second component thin layer and the second component thick layer are independently N1 x N2 y N3z Q q .
[0041] N1 includes any one of Ti, Cr, Zr, Hf, W or Mo.
[0042] N2 includes Al.
[0043] N3 includes any one of Ti, Cr, Zr, Hf, V, Ta, Nb, W, Mn, Mo or Si, or a combination of at least two of them. Typical but non-limiting combinations include a combination of Ti and Cr, a combination of Zr and Hf, a combination of V and Ta, a combination of Nb and W, a combination of Ti, Cr, Zr and Hf, a combination of Ta, Nb, W, Mn, Mo and Si, or a combination of Ti, Cr, Zr, Hf, V, Ta, Nb, W, Mn, Mo and Si.
[0044] Q is any one of N, O, C or B or a combination of at least two thereof. Typical but non-limiting combinations include a combination of N and C, a combination of N and B, a combination of C and B, or a combination of N, C and B.
[0045] And x>0.3, y>0.3 or y=0, z≤0.2, and x+y+z=1.
[0046] When Q is N and / or C, 0.95≤q≤1.05.
[0047] When Q is 0, 1.45≤q≤1.55.
[0048] When Q is B, 1.95≤q≤2.05.
[0049] M1 and N1 are the main elements, which are conducive to forming the main phase components and microstructures of the dual-periodic nanostructure coating. Exemplarily, when M and Q are independently nitrogen, when M1 and N1 are both Ti, the first component thick layer, the second component thin layer, the first component thin layer and the second component thick layer are all TiN coatings (such as TiAlN, TiSiN, etc.), which have the characteristics of high hardness; when M1 is Ti and N1 is Mo, the first component thick layer and the first component thin layer are TiN coatings, which have the characteristics of high hardness and wear resistance; the second component thin layer and the second component thick layer are MoN coatings, which have the effects of improving lubrication, reducing cutting force and improving cutting conditions.
[0050] M2 and N2 elements are the main strengthening elements, and Al can alloy and strengthen the coating, thereby improving the performance of the coating.
[0051] M3 and N3 are secondary strengthening elements that can further improve the cutting performance of the coating under specific working conditions. For example, Ta and Nb can reduce the hardness attenuation at high temperatures and are suitable for dry cutting without coolant; Si can form nanocrystals, while V and Cr can further refine the coating grains and improve the hardness of the coating by hindering the epitaxial growth of the coating.
[0052] In a second aspect, the present invention provides a method for preparing a double-periodic nanostructured coating, the preparation method comprising the following steps:
[0053] The physical vapor deposition method is adopted to sequentially deposit periodic coating units on the surface of the substrate to obtain the double-periodic nanostructure coating described in the first aspect.
[0054] The periodic coating unit includes a first component thick layer, a second component thin layer, a first component thin layer and a second component thick layer which are stacked.
[0055] Preferably, the physical vapor deposition device used in the physical vapor deposition comprises:
[0056] A rotating disk is used to fix the substrate; a first component target material and a second component target material are evenly placed around the rotating disk; a sputtering surface of the first component target material and a sputtering surface of the second component target material are respectively facing the surface to be coated of the substrate, and baffles capable of controlling the opening and closing size are independently arranged between the first component target material and the rotating disk, and between the second component target material and the rotating disk.
[0057] Preferably, the physical vapor deposition includes: fixing the substrate on a rotating disk, heating it to the process temperature under vacuum conditions, introducing argon gas for etching, and then introducing argon gas and / or reaction gas for coating deposition; when the surface to be coated of the substrate faces the first component target, the surface atoms of the first target are ionized under the action of high temperature and electric arc, and the ions move toward the surface to be coated of the substrate under the action of negative bias voltage to form a first component thin layer or a first component thick layer; when the surface to be coated of the substrate faces the second component target, the surface atoms of the second target are ionized under the action of high temperature and electric arc, and the ions move toward the surface to be coated of the substrate under the action of negative bias voltage to form a second component thin film and a second component thick layer, and the temperature is reduced to obtain the double-periodic nanostructure coating.
[0058] Preferably, the process temperature is 450°C-650°C, for example, 450°C, 500°C, 550°C, 600°C or 650°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0059] Preferably, the negative bias voltage is -30V to -150V, for example, -30V, -50V, -80V, -100V, -120V or -150V, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0060] Preferably, the reaction gas includes any one of nitrogen, oxygen or acetylene or a combination of at least two of them, wherein nitrogen, oxygen or acetylene respectively provide nitrogen, oxygen and carbon elements in the physical vapor deposition process.
[0061] When only argon gas is introduced during the physical vapor deposition process, the argon gas serves to maintain the existence of the arc, glow or plasma and does not participate in the elemental reaction of the deposition.
[0062] Preferably, during the physical vapor deposition process, the relative evaporation and ionization rates of the target elements can be controlled by controlling the target currents of the first component target and the second component target, thereby controlling the deposition rates of the first component and the second component on the substrate surface, and further controlling the thicknesses of the first component thick layer, the second component thin layer, the first component thin layer, and the second component thick layer, respectively.
[0063] Optionally, the target current ranges from 140A to 230A, for example, 140A, 150A, 160A, 180A, 200A, 210A or 230A, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0064] The baffle between the first component target and the rotating disk is the first baffle, and the baffle between the second component target and the rotating disk is the second baffle. When the first baffle is opened to the maximum, the second baffle is opened to the minimum but not closed. At this time, after the rotating disk rotates one circle, a thick layer of the first component and a thin layer of the second component are obtained; conversely, when the second baffle is opened to the maximum, the first baffle is opened to the minimum but not closed, and after the rotating disk rotates one circle, a thin layer of the first component and a thick layer of the second component are obtained. Therefore, by setting a suitable rotating disk speed and baffle opening and closing cycle, the first component thick layer, the second component thin layer, the first component thin layer and the second component thick layer of the desired thickness and thickness correlation can be obtained.
[0065] In the present invention, the time that the surface to be coated of the substrate stays in front of different metal targets can be controlled by adjusting the rotation speed of the rotating disk, thereby controlling the deposition thickness; optionally, the quantitative relationship between the first component target and the second component target can be appropriately adjusted to change the relative thickness of the first component layer and the second component layer.
[0066] Preferably, during the physical vapor deposition, the rotation speed of the rotating disk is T1 r / min; the opening and closing frequency of the baffle is T2 times / min; then T1=2T2.
[0067] Preferably, the substrate is pretreated before physical vapor deposition to obtain a coating surface that is conducive to coating deposition and adhesion.
[0068] Optionally, the pretreatment method includes any one of machining, sandblasting, demagnetization or cleaning, or a combination of at least two of them.
[0069] Optionally, the mechanical processing includes: processing the substrate to a desired workpiece shape and size through grinding, polishing and other processes, and smoothing the polished surface to improve the bonding strength between the coating and the substrate.
[0070] Optionally, the sandblasting includes: passivating the overly sharp and uneven edges of the substrate surface to be coated by dry or wet blasting, reducing the internal stress of the coating film on the edges, reducing crack generation and coating peeling, smoothing the surface to be coated, and reducing surface scratches to facilitate coating deposition.
[0071] Optionally, the demagnetization includes: removing the magnetism of the substrate itself by applying a certain changing magnetic field, reducing the adhesion of magnetic dust on the surface of the substrate to be coated, reducing the influence of the substrate magnetism on the electric field magnetic distribution in the furnace, and improving the bonding strength of the dual-period nanostructured coating and the stability of the coating uniformity.
[0072] Optionally, the cleaning includes: using pure water, alkaline cleaning agent, ultrasound, high-temperature drying and other methods to clean the dirt and dust on the surface of the substrate to be coated, which is beneficial to the deposition and adhesion of the double-period nanostructured coating and improves the bonding strength.
[0073] In a third aspect, the present invention provides a cutting tool, comprising the dual-periodic nanostructure coating described in the first aspect.
[0074] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0075] Compared with the prior art, the present invention has the following beneficial effects:
[0076] The dual-period nanostructured coating provided by the present invention has both the superhard effect of the thin periodic coating and the high toughness and high bonding strength of the thick periodic coating by specifically setting the first component thick layer, the second component thin layer, and the thickness relationship between the first component thin layer and the second component thick layer. When the dual-period nanostructured coating is applied to cutting tools, the service life of the cutting tools can be significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] Figure 1 This is a schematic diagram of the structure of the double-periodic nanostructured coating provided in Example 1 of the present invention.
[0078] Figure 2 It is a top view of the structure of the physical vapor deposition device in a specific embodiment of the present invention, and the arrows in the figure indicate the opening and closing directions of the baffles.
[0079] Among them: 1, thick layer of first component; 2, thin layer of second component; 3, thin layer of first component; 4, thick layer of second component; 5, target material of first component; 6, target material of second component; 7, first baffle; 8, second baffle; 9, rotating disk. DETAILED DESCRIPTION
[0080] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0081] In a specific embodiment of the present invention, a WC-based cemented carbide blade is used as a substrate, wherein the Co content is 10wt%, the VC content is 0.2wt% and the balance is WC. The average particle size of WC, Co and VC is 0.8μm, and the blade model is WNMG080408-LM. The WC-based cemented carbide blade is pretreated before use, specifically: the surface of the WC-based cemented carbide blade is mechanically flat ground; a double-end face grinder equipped with a 600-mesh diamond grinding wheel is used for polishing to obtain a flat and smooth blade surface to be attached, and the blade tip clamping height is 4±0.01mm; a mixed liquid with Al2O3 powder is sprayed with a high-pressure water gun to passivate the blade edge radius to 30μm; the blade is ultrasonically cleaned with high-purity water, and then dried at high temperature, and then a double-period nanostructure coating is set using the method in the following embodiment and comparative example.
[0082] The physical vapor deposition apparatus for the following embodiments and comparative examples is as follows: Figure 2 The device shown includes: a rotating disk 9, which is used to fix the substrate; the first component target 5 and the second component target 6 are evenly placed around the rotating disk; the sputtering surface of the first component target 5 and the sputtering surface of the second component target 6 are respectively facing the surface to be coated of the substrate, and baffles capable of controlling the opening and closing size are independently arranged between the first component target 5 and the rotating disk 9, and between the second component target 6 and the rotating disk 9. The baffle between the first component target 5 and the rotating disk 9 is the first baffle 7, and the baffle between the second component target 6 and the rotating disk 9 is the second baffle 8. When the first baffle 7 is opened to the maximum, the second baffle 8 is opened to the minimum but not closed. At this time, after the rotating disk 9 rotates one circle, the first component thick layer and the second component thin layer are obtained; conversely, when the second baffle 8 is opened to the maximum, the first baffle 7 is opened to the minimum but not closed. After the rotating disk 9 rotates one circle, the first component thin layer and the second component thick layer are obtained.
[0083] The physical vapor deposition using the device comprises: fixing a substrate on a rotating disk, heating to a process temperature under vacuum conditions, introducing argon gas for etching, and then introducing argon gas and / or reaction gas for coating deposition; when the surface to be coated of the substrate faces a first component target material, atoms on the surface of the first target material are ionized under the action of high temperature and electric arc, and ions move toward the surface to be coated of the substrate under the action of negative bias voltage to form a first component thin layer or a first component thick layer; when the surface to be coated of the substrate faces a second component target material, atoms on the surface of the second target material are ionized under the action of high temperature and electric arc, and ions move toward the surface to be coated of the substrate under the action of negative bias voltage to form a second component thin layer and a second component thick layer, and cooling is performed to obtain the double-periodic nanostructure coating.
[0084] The testing method in the specific implementation manner of the present invention includes:
[0085] (I) A transmission electron microscope (TEM) is used for measurement, and the magnification of the TEM is set to 1.25 million times. The first component thick layer, the second component thin layer, the first component thin layer and the second component thick layer with different light and dark stripes can be clearly observed in the field of view. In combination with the EDS module of the TEM equipment, the first component thick layer, the second component thin layer, the first component thin layer and the second component thick layer are respectively analyzed by component point analysis to obtain the atomic ratio content of each element in the coating, and 5 measurement points are selected and the average value is taken as the composition of each layer of the coating; under the field of view of 1.25 million times, 5 areas are selected for photography, and the thickness of the first component thick layer, the second component thin layer, the first component thin layer and the second component thick layer in each figure is counted according to the measurement results of the ruler, and the average value is taken as the single layer thickness of each layer of the coating.
[0086] (II) The coating hardness was measured using a nanoindenter, Anton-Paar TriTec UNHT3, with a maximum load of 20 mN, a loading and unloading time of 30 s, and a holding time of 5 s. The instrument measured the relationship between the loading force and the indentation depth, and automatically calculated the hardness (GPa) of the coating. The measurement was repeated 16 times in a 4×4 matrix mode, and the curves and values with excessive deviations were deleted, and the average value was taken as the hardness at room temperature.
[0087] (III) Using TRIBO Millennium 200 scratch tester to measure the strength of the coating adhesion: using a conical diamond indenter with a smooth tip to scratch the coating surface at a certain speed, while gradually increasing the vertical pressure of the indenter, the minimum pressure of the coating cracking is used to characterize the strength of the coating film-based adhesion; the measurement parameters are: scratch length of 12mm, scratch speed of 5mm / min, indenter pressure of 0N-120N, loading speed of 50N / min. According to the acoustic signal of coating cracking collected synchronously in the scratch loading test, the change of friction force of the indenter scratching the substrate, the cracking of the coating surface and the pressure corresponding to its position, etc., the critical load force when the coating cracks is determined, and the average of the three measurements is the coating film-based adhesion described in the present invention.
[0088] (IV) Cutting test of 304 stainless steel: the base hardness of 304 stainless steel is 220HB, the cutting speed is 180m / min, the feed rate is 0.2mm / r, the cutting depth is 2mm, and coolant is used for water cooling during the cutting process; the cutting is paused for 1min every time to observe whether the blade is chipped or the flank wear value exceeds 0.3mm; cutting is continued until the blade is chipped or the flank wear exceeds 0.3mm, which is the cutting life of the blade; each group of tests is conducted 3 times, and the average value is taken as the corresponding cutting life.
[0089] Example 1
[0090] This embodiment provides a Figure 1 The double-periodic nanostructure coating shown includes a periodic structure arranged in layers; the periodic structure includes a first component thick layer 1, a second component thin layer 2, a first component thin layer 3 and a second component thick layer 4 arranged in layers.
[0091] The preparation method of the double-period nanostructure coating comprises:
[0092] (1) The substrate is clamped on a rotating disk of a physical vapor deposition device (arc ion plating equipment furnace), and a first component target and a second component target are evenly placed on the circumference of the rotating disk. The ratio of the first component target to the second component target is 1:1; the first component of the first component target is Ti 0.35 Al 0.55 Nb 0.1 The second component of the second component target is Ti 0.35 Al 0.65 ;
[0093] The rotating disk speed was set to 2 r / min, and the arc ion plating equipment furnace was evacuated to 5 × 10 -4mbar, and the substrate surface is heated to 500°C and kept stable by the heating device in the furnace of the arc ion plating equipment; Ar gas is introduced into the furnace of the arc ion plating equipment to maintain the Ar partial pressure in the furnace at 0.05mbar to maintain the generation of the metal target arc, and the Ar ionization chamber switch is turned on, and the negative bias voltage is set to -200V, so that the ionized Ar ions bombard the blade substrate at a high speed under the action of the electric field, and the etching is continued for 30 minutes.
[0094] (2) Maintaining the Ar partial pressure unchanged, the reaction gas N2 is introduced for coating deposition, wherein the N2 gas partial pressure is 0.05 mbar; the deposition negative bias voltage is set to -60 V, the arc evaporation device of the first component target and the second component target is started, and the target current of the first component target is set to 180 A, and the target current of the second component target is set to 180 A; during the deposition process, as the turntable rotates, when the surface of the substrate to be coated faces the first component target, the atoms of the first component target are ionized under the action of high temperature and arc, and the ions move toward the surface of the substrate to be coated under the action of negative bias, and react and deposit into a first component thick layer or a first component thin layer; when the surface of the substrate to be coated faces the second component target, the second component target is also reacted and deposited into a second component thick layer or a second component thin layer; at the same time, the opening and closing frequency of the baffle is set to 1 time / min. When the first baffle is opened to the maximum 100%, the opening amplitude of the second baffle is set to 50%. At this time, the thickness of the first component thick layer deposited after the turntable rotates one circle is greater than the thickness of the second component thin layer. On the contrary, when the baffle of the second baffle is opened to the maximum of 100%, the opening amplitude of the first baffle is set to 50%. At this time, the thickness of the first component thin layer deposited after the turntable rotates one circle is less than the thickness of the second component thick layer. Each baffle is opened and closed once every two rotations of the rotating disk. The turntable is kept rotating continuously, the baffles are kept opened and closed, and the periodic deposition is performed for 60 minutes to obtain the double-periodic nano multilayer structure coating.
[0095] (3) After stopping the deposition, Ar gas is introduced to maintain the pressure in the furnace at 200 mbar, and the fan in the furnace is turned on. The coating furnace is cooled rapidly. When the temperature is cooled to below 100° C., the coating furnace is taken out of the furnace to obtain the following: Figure 1 The double-periodic nanostructured coating is shown.
[0096] The first target material, the second target material, the rotating disk speed, the minimum opening amplitude of the baffle, the target current of the first target material, the target current of the second target material and the reaction atmosphere gas used in Example 2 to Example 18 and Comparative Example 1 are shown in Table 1; the compositions of the first component and the second component in the obtained dual-period nanostructure coating are shown in Table 2; the thickness of each layer is shown in Table 3, and the relationship between the thickness of each layer is shown in Table 4, wherein the thickness of the first component thick layer is a1 nm, the thickness of the second component thin layer is b1 nm, the thickness of the first component thin layer is a2 nm, the thickness of the second component thick layer is b2 nm, the total thickness of the first component thick layer and the second component thin layer is c1 nm, the total thickness of the first component thin layer and the second component thick layer is c2 nm, and the total thickness of the first component thick layer, the second component thin layer, the first component thin layer and the second component thick layer is d nm; the test results of room temperature hardness, bonding strength and cutting life are shown in Table 5, the qualified value of room temperature hardness should be greater than 30 GPa, the bonding strength should be greater than 60 N, and the cutting life should be greater than 20 min.
[0097] Table 1
[0098]
[0099]
[0100] Table 2
[0101]
[0102]
[0103] Table 3
[0104]
[0105] Table 4
[0106]
[0107] Table 5
[0108]
[0109]
[0110] From Table 1 to Table 5, we can see that:
[0111] (1) Example 1 is the double-periodic nanostructured coating described in the present invention, and the baffle amplitude is 50%. Due to the shielding of the baffle, the thickness of the single layer a2 and b1 is thinner than that of a1 and b2, so that their thickness relationship satisfies the relationship: 1.5≤a1 / a2≤3, 1.5≤b2 / b1≤3, 1.5≤a1 / b1≤3, 1.5≤b2 / a2≤3. Comparative Example 1 is an existing single-periodic nanostructured coating. During the coating process, the baffle is always in a 100% open state, which has no effect on the coating deposition. The thickness of each layer a1, a2, b1, and b2 is similar, and the thickness relationship is not satisfied. Since the single layer thickness of a2 and b1 in Example 1 is only half of that in Comparative Example 1, under the condition that other conditions remain unchanged, its nano-superhard effect is greatly improved, and the overall hardness of the coating is significantly improved. Under the premise of qualified bonding force and no chipping, the cutting life of the blade is comprehensively improved; Comparative Example 1 has a low overall cutting life due to its unqualified hardness, which does not meet the performance requirements.
[0112] (2) Both Example 2 and Example 17 are double-periodic nanostructured coatings, but the baffle amplitudes of the two are different, which makes the coating structures of the two different. The single-layer thickness of Example 2 satisfies the relationship: a1 / a2≥1.5, b2 / b1≥1.5, a1 / b1≥1.5, b2 / a2≥1.5; the single-layer thickness of Example 17 is: a1 / a2<1.5, b2 / b1<1.5, a1 / b1<1.5, b2 / a2<1.5. Compared with Example 2, the thickness difference between the single layers of the coating of Example 17 is small, the superhard effect of the thin single layer cannot be significantly improved, and the overall thickness is thicker, so its overall hardness, wear resistance and cutting life are worse than those of Example 2, but still meet the performance requirements.
[0113] (3) Both Example 3 and Example 18 are double-periodic nanostructured coatings, but the baffle amplitudes of the two are different, which makes the coating structures of the two different. The single-layer thickness of Example 3 satisfies the relationship: a1 / a2≤3, b2 / b1≤3, a1 / b1≤3, b2 / a2≤3; the single-layer thickness of Example 18 is: a1 / a2>3, b2 / b1>3, a1 / b1>3, b2 / a2>3. Compared with Example 3, the thickness difference between the single layers of the coating of Example 18 is large. The first component thin layer and the second component thin layer are too thin. At this time, the microstructures such as the phase composition and lattice constant of the second component thin layer will tend to grow epitaxially on the basis of the first component thick layer, causing the second component thin layer to undergo lattice distortion, from the lattice constant of the second component to the lattice constant of the first component. Although this will increase the hardness of the coating, it will also cause the coating's resistance to plastic deformation to decline, thereby reducing the coating's bonding strength. This makes the bonding force and overall cutting life of Example 18 lower than that of Example 3, but still meets the performance requirements.
[0114] (4) In Example 4, the thickness of each of the first component thick layer, the second component thin layer, and the first component thin layer and the second component thick layer is greater than 4nm, and c1>12nm, c2>12nm, and d>24nm. In Example 5, the thickness of the first component thin layer is less than 4nm, and the thickness of the second component thin layer is less than 4nm, and c1<12nm, c2<12nm, and d<24nm. Excessively thin first component thin layers and second component thin layers tend to have excessive lattice distortion due to their tendency to epitaxial growth; excessively small c1, c2, and d increase the number and density of nano-coating interfaces. These all reduce the bonding strength of the coating, making the bonding strength and overall cutting life of Example 5 lower than those of Example 4, but still meeting the performance requirements.
[0115] (5) In the first component thick layer, the second component thin layer, the first component thin layer and the second component thick layer of Example 6, the thickness of each layer is less than 70nm, and c1<100nm, c2<100nm, and d<200nm. The thickness of the first component thick layer and the second component thick layer of Example 7 is greater than 70nm, and c1>100nm, c2>100nm, and d>200nm. The excessively thick nanolayer makes the nano-superhard effect insignificant, and the overall hardness of the coating decreases, so that the hardness and overall cutting life of Example 7 are lower than those of Example 6, but still meet the performance requirements.
[0116] (6) In Example 8, the gas introduced is acetylene, which reacts with the target ions to deposit a carbide coating; in Example 9, the gas introduced is oxygen, which reacts with the target ions to deposit an oxide coating; in Example 10, the gas introduced is argon, which is used to maintain the arc and does not react with the target ions to deposit a boride coating. The thickness of each nano single layer in each embodiment satisfies the thickness relationship, and the overall hardness, bonding strength, and cutting life of the coating are all qualified.
[0117] (7) The contents of the coating components M1 and N1 (both are Ti) in Example 11 are greater than 0.3; the contents of the coating components M1 and N1 (both are Ti) in Example 14 are less than 0.3, which results in insufficient Ti content in the main phase (i.e., TiN phase) of each layer in Example 14, and the coating cannot form a complete cubic TiAlN main phase structure, resulting in the precipitation of some impurity phases such as hexagonal AlN phase. The precipitated phase has a lower hardness than the main phase, and at the same time destroys the coating structure and reduces the coating bonding strength, so that the overall hardness, bonding strength, and cutting life of Example 14 are lower than those of Example 11, but still meet the performance requirements.
[0118] (8) The contents of the coating components M2 and N2 (both Al) in Example 12 are greater than 0.3; the contents of the coating components M2 and N2 (both Al) in Example 15 are less than 0.3. This makes the relative content of Al in each layer of Example 15 too low, and the coating cannot be fully alloyed and strengthened, so that the overall hardness, bonding strength, and cutting life of Example 15 are lower than those of Example 12, but still meet the performance requirements.
[0119] (9) The coating component M3 (Ta) content in Example 13 is less than 0.2; the coating component M3 (Ta) content in Example 16 is greater than 0.2, which causes the layers of Example 16 to dissolve excessive Ta, thereby precipitating a portion of TaN phase in the TiAlN cubic phase. The precipitated phase has a lower hardness than the main phase, and at the same time destroys the coating structure and reduces the coating bonding force, so that the overall hardness, bonding force, and cutting life of Example 16 are all lower than those of Example 13, but still meet the performance requirements.
[0120] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A double-periodic nanostructured coating, characterized in that: The double-periodic nanostructure coating comprises periodic coating units stacked in sequence; The periodic coating unit includes a first component thick layer, a second component thin layer, a first component thin layer and a second component thick layer which are stacked; The thickness of the first component thick layer is greater than the thickness of the first component thin layer, and the thickness of the first component thick layer is greater than the thickness of the second component thin layer; the thickness of the second component thick layer is greater than the thickness of the second component thin layer, and the thickness of the second component thick layer is greater than the thickness of the first component thin layer.
2. The double-periodic nanostructure coating according to claim 1, characterized in that: The thickness of the first component thick layer is a1 nm, the thickness of the second component thin layer is b1 nm, the thickness of the first component thin layer is a2 nm, and the thickness of the second component thick layer is b2 nm; The thickness of the first component thick layer, the thickness of the second component thin layer, the thickness of the first component thin layer and the thickness of the second component thick layer satisfy: 1.5≤a1 / a2≤3, 1.5≤b2 / b1≤3, 1.5≤a1 / b1≤3, 1.5≤b2 / a2≤3.
3. The double-periodic nanostructure coating according to claim 1 or 2, characterized in that: The thickness of the first component thick layer is 4nm-70nm; and / or, the thickness of the second component thin layer is 4nm-70nm; and / or, the thickness of the first component thin layer is 4nm-70nm; And / or, the thickness of the second component is 4nm-70nm.
4. The double-periodic nanostructure coating according to claim 3, characterized in that: The total thickness of the first component thick layer and the second component thin layer is 12nm-100nm; and / or, the total thickness of the first component thin layer and the second component thick layer is 12 nm-100 nm; And / or, the thickness of the first component thick layer, the second component thin layer, and the total thickness of the first component thin layer and the second component thick layer is 24 nm-200 nm.
5. The double-periodic nanostructure coating according to claim 1, characterized in that: The first components in the first component thin layer and the first component thick layer are independently M1 a M2 b M3 c M m , M1 includes any one of Ti, Cr, Zr, Hf, W or Mo, M2 includes Al, M3 includes any one of Ti, Cr, Zr, Hf, V, Ta, Nb, W, Mn, Mo or Si or a combination of at least two, M is any one of N, O, C or B or a combination of at least two; and a>0.3, b>0.3 or b=0, c≤0.2, and a+b+c=1; When M is N and / or C, 0.95≤m≤1.05; when M is O, 1.45≤m≤1.55; when M is B, 1.95≤m≤2.
05.
6. The double-periodic nanostructure coating according to claim 1, characterized in that: The second components in the second component thin layer and the second component thick layer are independently N1 x N2 y N3 z Q q , N1 includes any one of Ti, Cr, Zr, Hf, W or Mo, N2 includes Al, N3 includes any one of Ti, Cr, Zr, Hf, V, Ta, Nb, W, Mn, Mo or Si or a combination of at least two, Q is any one of N, O, C or B or a combination of at least two; and x>0.3, y>0.3 or y=0, z≤0.2, and x+y+z=1; When Q is N and / or C, 0.95≤q≤1.05; when Q is O, 1.45≤q≤1.55; when Q is B, 1.95≤q≤2.
05.
7. A method for preparing a double-periodic nanostructured coating, characterized in that: The preparation method comprises the following steps: Using a physical vapor deposition method, periodic coating units are sequentially deposited on the surface of a substrate to obtain the double-periodic nanostructure coating according to any one of claims 1 to 6; The periodic coating unit includes a first component thick layer, a second component thin layer, a first component thin layer and a second component thick layer which are stacked.
8. The preparation method according to claim 7, characterized in that: The physical vapor deposition device used in the physical vapor deposition comprises: A rotating disk, the rotating disk is used to fix the substrate; The first component target and the second component target are evenly placed around the rotating disk; the sputtering surface of the first component target and the sputtering surface of the second component target are respectively facing the surface to be coated of the substrate, and baffles capable of controlling the opening and closing size are independently arranged between the first component target and the rotating disk and between the second component target and the rotating disk.
9. The preparation method according to claim 8, characterized in that: During the physical vapor deposition, the rotation speed of the rotating disk is T1 r / min; the opening and closing frequency of the baffle is T2 times / min; Then T1=2T2.
10. A cutting tool, characterized in that: The cutting tool comprises the double-periodic nanostructure coating according to any one of claims 1-6.